SCREENING OF TEN HERBAL EXTRACTS TO COMPARE AND INVESTIGATE EFFECT ON GLUCOSE LOWERING AND ANOREXIC ACTIVITY IN WISTAR RATS - Jani, Deepti Kaushalkumar; Goswami, Sunita (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Metabolic disorders are of growing concern with increasing quest for herbal medicines as treatment option. The current study is planned to screen ten herbal extracts, prepared from parts of chosen six herbal plants, to compare and investigate their antihyperglycemic and anorexic potential. Methods: Qualitative phytochemical investigation was done as per standard procedures. Acute oral toxicity study performed as per OECD 420 guideline. Glucose Tolerance Test (method optimization) was performed to select appropriate glucose load to induce hyperglycemia. Antihyperglycemic activity was evaluated by Glucose Tolerance Test (single dose and multiple dose study) and anorexic potential was screened by food intake measurement using Wistar rats. Results: All herbs were found safe in acute oral toxicity study. Glucose Tolerance Test method optimization study signaled use of 3 g/kg glucose load for induction of hyperglycemia in single and multiple dose studies. In single dose study, L. acutangula fruit extract and in multiple dose study, S. melongena, M. oleifera & R. communis extracts were found to produce significant glucose lowering effect as compared to glucose control group. Results of food intake measurement showed significant appetite suppression with extracts of W. somnifera, S. melongena, M. oleifera & R. communis. Â  Conclusion: Present study throws light on the effectiveness of experimental herbal extracts as antihyperglycemic and anorexic agents. This also, helps in identifying potent indigenous herbs for further study.Â 